IMPLEMENTASI PEMBELAJARAN SENI GERAK DAN LAGU ANAK USIA DINI DI TK KHADIJAH 21 TEGALDLIMO BANYUWANGI - Ria octa viana; Riris Wahyuningsih (Institut Agama Islam Nahdlatul Ulama Tuban, 2023)
Learning movements and songs in early childhood is very useful to stimulate child development, especially children's physical and motor development. In addition, learning movements and songs also develops 6 aspects of children's ability development. TK Khadijah 21 Banyuwangi is a kindergarten educational institution that develops all the basic potential of children, this is in accordance with the vision, mission and goals of TK Khadijah 21 Banyuwangi. Vision desires to create an institution that excels in quality students based on religious education, and produce students who are literate, creative, innovative and character. The way to achieve this vision is by organizing learning that instills religious values and charity, as well as creative, innovative and fun learning. Efforts to realize the vision and mission at TK Khaidjah 21 Tegaldlimo Banyuwangi create a learning program for movement arts and songs that can be made into excellence at TK Khadijah 21 Tegaldlimo Banyuwangi.